2017
DOI: 10.1051/kmae/2017014
|View full text |Cite
|
Sign up to set email alerts
|

Salinity tolerance of marbled crayfishProcambarus fallaxf.virginalis

Abstract: -Eastern Europe comprises a significant part of the native ranges for indigenous crayfish species (ICS) belonging to the genus Astacus. This region has been largely overlooked by astacologists and considered relatively immune to the impacts of non-indigenous crayfish species (NICS). The recent discovery of two marbled crayfish Procambarus fallax f. virginalis populations in Ukraine has changed this view. Increased propagule pressure (mainly due to pet trade) has raised concerns of NICS which may negatively imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…While this is feasible and cost-effective for the hatchery and nursery stages, closed systems would represent a major economic disadvantage for the growout stage, which requires large surfaces. However, marbled crayfish are known to have very low salinity tolerance 45 . Based on the available information 45 12.206505E) was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…While this is feasible and cost-effective for the hatchery and nursery stages, closed systems would represent a major economic disadvantage for the growout stage, which requires large surfaces. However, marbled crayfish are known to have very low salinity tolerance 45 . Based on the available information 45 12.206505E) was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Freshwater crayfish tolerate saline water to some extent (e.g., Holdich et al, 1997;Vesely et al, 2017) but have not been reported to reproduce in high salinity waters (Holdich et al, 1997). However, low-saline estuaries and coastal areas could potentially act as invasion corridors between rivers (Dobrzycka- Krahel et al, 2017;Vesely et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, low-saline estuaries and coastal areas could potentially act as invasion corridors between rivers (Dobrzycka- Krahel et al, 2017;Vesely et al, 2017). Experimental signal crayfish introduction were carried out in the Finnish coastal area of Baltic Sea (salinity 1.5-6‰) in 1970's and 1980's, but no observations of established populations have so far been made (Järvenpää T. pers comm).…”
Section: Discussionmentioning
confidence: 99%
“…Marbled crayfish and P. fallax were not yet found in brackish water. However, laboratory experiments revealed that marbled crayfish can survive salt concentration up to 18 ppt for more than 80 days but growth and reproduction stops at 6 ppt (Veselý et al, 2017).…”
Section: Procambarus Fallaxmentioning
confidence: 99%
“…Both crayfish probably do not burrow by preference but when the water table is lowered in the dry season (Hobbs, 1981;Jones et al, 2009;Chucholl et al, 2012;van der Heiden, 2012), Marbled crayfish and P. fallax were not yet found in brackish water. However, laboratory experiments revealed that marbled crayfish can survive salt concentration up to 18 ppt for more than 80 days but growth and reproduction stops already at 6 ppt (Veselý et al, 2017).…”
Section: Procambarus Fallaxmentioning
confidence: 99%